Peran Pendamping Program Keluarga Harapan dalam Meningkatkan Kunjungan K1-K4 Ibu Hamil ke Pelayanan Kesehatan - Antono, Shella Putri Permadani Hardi; Rokhmah, Dewi; Nafikadini, Iken (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2019)
Background: Family Hope Program (PKH) as referred to as conditional cash transfer is a government poverty alleviation program by providing conditional cash money to induces healthy behavior especially pregnant, lactating mother and children under 5 years nutritional status in poor families. This program is assisted by field staff to facilitate PKH participants to comply antenatal care visits of pregnant mothers and improving nutritional status of children under five years. This study aims to explore the perception of PKH participants regarding the role of field staffs as a motivator, facilitator, educator, and mediator in assisting participants.Method:This is a qualitative study using in-depth interviews to nine pregnant mothers (as PKH participants) who lived in Sumbermalang, Situbondo District. The informants were selected purposively with inclusion criteria is pregnant mothers as well as their husbands who have been participating in PKH program for more than 2 years. In-depth interviews were also conducted to health providers (village midwives) and field staffs of PKH. Data were analyzed using thematic content analysis.Results: The characteristics of informants were mostly around 20-25 years old, 7-9 months of pregnancy, as housewive and husbands’ occupation was a building construction. Most informants say that the field staffs have facilitated them to improve their behavior to visit health center or village midwives to control their pregnancy, and also provided health education including motivated pregnant mother to consume ferrum tablet completely as well as other medicine. There were no obstacles arising in visiting health center to control their pregnancy and children. PKH field staff roles were necessary as a facilitator, motivator, mediator, and educator of PKH participants in order to help participants to change their behavior. Increase coordination among PKH field staffs and health workers including village midwives is needed to run this program smoothly.